Left‐behind villages, left‐behind children: Migration and the cognitive achievement of rural children in China. Issue 8 (27th May 2019) - Xie, Wubin; Sandberg, John; Huang, Cheng; Uretsky, Elanah
Abstract: Although the potential effects of migration on the cognitive development of children in origin communities reflect both household‐ and community‐level processes, few studies have examined how community‐level migration affects child cognitive development. By applying multilevel methods to nationally representative data of 2, 248 children from 427 villages in China, we examine whether village migration intensity influences child cognitive ability and if so, what accounts for this influence. The findings suggest lower cognitive achievement in communities that experience high migration intensity. Living in a community with a large proportion of people who have migrated away from the community is associated with a 3.57‐unit decrease in verbal scores and a 1.54‐unit decrease in maths scores, which is equivalent to missing 1.67 and 0.87 years of schooling, respectively. A possible explanation for this effect is the change in demographic composition such that communities are depleted of better educated adults.